Relationships between geomagnetic Ар-indeх and parameters of the acupuncture points as well as neuroendocrine-immune complex in patients with its dysfunction - R. Tserkovniuk; A. Gozhenko; T. Korolyshyn; M. Kovbasnyuk; V. Hubyts'kyi; V. Kikhtan; V. Fil; A. Anchev; W. Zukow; R. Yanchij; I. Popovych (Kazimierz Wielki University, 2021)
Background. Back in 1990, YuP Limansky hypothesized acupuncture points (AP) as polymodal receptors of the ecoceptive sensitivity system. In the process of hypothesis development in 2003 an existence of separate functional system of regulation of electromagnetic balance of organism has been substantiated and a working conception of light therapy has been formulated. In line with this hypothesis, we set out to analyze the relationships between the disturbances of the geomagnetic field (Ap-index) and the electrical conductivity of a number of AP, on the one hand, and the parameters of the neuroendocrine-immune complex in patients with its dysfunction, on the other. Material and methods. The object of observation were 21 men (24-63 y) and 20 women (30-72 y) with neuroendocrine-immune complex dysfunction. Each patient was tested twice with an interval of 4 days. Retrospectively we recorded the geomagnetic Ap-Index on the day of testing and during the previous 7 days, using resource https://www.spaceweatherlive.com/. Recorded the electrical conductivity of 9 pairs of AP, electroencephalogram (EEG) and heart rate variability (HRV) parameters, determined the plasma level of cortisol, triiodothyronine and testosterone, the content of lymphocytes expressing CD3, CD4, CD25, CD8, CD22 and CD56 receptors, the serum level of circulating immune complexes, immunoglobulins classes M, G, A as well as C-reactive protein, IL-1β and IL-6. The state of phagocytic function of neutrophils estimated by microbial count and phagocytic and killing indices against Staphylococcus aureus and Escherichia coli. Results. During the week, the average level of Ap-index ranged from 7 to 13 nT. Maximum coefficients of multiple correlation with APs parameters were detected for Ap-index on 6 day before (R=0,552) and on the day of testing (R=0,470), with EEG parameters on the eve of registration (R=0,708) and on 6 day before its (R=0,685), with immunity parameters on the eve of blood sampling (R=0,768) and on 5 day before its (R=0,758), with HRV&Hormonal parameters on 2 (R=0,506) and 7 (R=0,403) days before testing. The canonical correlation between Ap-indices for 7 days before and on the day of testing, and the parameters APs is 0,661; EEG parameters is 0,886; HRV&Hormonal parameters is 0,766 and immunity parameters is 0,921. APs parameter are closely related to the EEG (R=0,997) and HRV&Hormonal parameters (R=0,740). In turn, the immune parameters are closely related to the EEG (R=0,944) and HRV&Hormonal parameters (R=0,714). Conclusion. Disturbances of the geomagnetic field (Ap-index) causes a significant immediate modulating effect on the parameters of neuroendocrine-immune complex, apparently through acupuncture points as polymodal receptors of the ecoceptive sensitivity system.